Strategi Meningkatkan Keaktifan Belajar IPAS Peserta Didik Kelas IV SDN 30 Mataram melalui Media Puzzle Edukatif - Apriadi, Muh. Adi; Muntari; Muharrar, Ahmad (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aimed to improve student learning engagement in Natural and Social Sciences (IPAS) for fourth-grade students at SDN 30 Mataram through the use of educational puzzle media. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles, each including planning, implementation, observation, and reflection stages. The subjects of the study were 23 fourth-grade students, with data collected through learning engagement observation sheets, documentation, and field notes. The analysis results showed a significant increase in learning engagement, from an average of 61% in Cycle I to 87% in Cycle II. This improvement was evident in indicators such as participation in discussions, willingness to ask questions, ability to answer, and active involvement in completing puzzles with enthusiasm. Educational puzzle media, which combines elements of play and learning, proved effective in creating a fun and interactive learning environment, thereby encouraging students to engage more actively in the IPAS learning process. Thus, this media can be considered an innovative alternative for enhancing student motivation and learning engagement in elementary schools.